A Comparison of Student Engagement in Flipped, Active Lecture, and Online Counseling Courses. Issue 1 (2nd January 2022) - Merlin-Knoblich, Clare; Chase, Lauren; Smith, Joshua D.; Opiola, Kristie K.
ABSTRACT: A variety of teaching approaches have recently grown in popularity in counselor education, including flipped learning and online learning, yet no researchers have published comparisons of these course formats to traditional or active learning course formats in counselor education. In this study, we compared student course engagement in flipped, active lecture, and online course sections for same lifespan development counseling course. Flipped ( n = 24) and active lecture ( n = 44) participants reported statistically significantly higher engagement than online participants ( n = 21). Flipped participants also reported non-significantly higher engagement than active lecture and online participants. These findings both support and contrast with previous research in other disciplines.